Comprehensive assessment and performance enhancement of compressed air energy storage: thermodynamic effect of ambient temperature. (August 2022) - Liu, Qingshan; Liu, Yingwen; Liu, Hongjiang; He, Zhilong; Xue, Xiaodai
Abstract: In an adiabatic compressed air energy storage system, the significance of ambient temperature variation to determine the components' off-design operation and system performance was not clear yet. In this paper, a dynamic model of the concerned system considering off-design operation of components and real fluid behavior was established. Design and off-design performance of components and system, as well as the relationship between each component, were investigated under various ambient temperatures. The link between ambient temperature variation and system capacity was elucidated. Results showed that as ambient temperature declined, the total compression ratio of compressor unit increased, whereas the storage pressure of air chamber first increased, then reached a plateau. Compared to design condition, 4.83% higher turbine power and 7.53% higher round trip efficiency were obtained at higher ambient temperatures. At lower ambient temperatures, system efficiency was reduced by up to 4.85%, but output work remained practically unchanged. To improve the off-design performance at lower ambient temperatures, a control strategy of thermal energy storage was proposed. The round trip efficiency and output work were improved by 7.7%–11.3% and 5.3%–7.2% with the proposed operation strategy, which were 5.9%–7.0% and 4.5%–4.8% higher than those under design condition.